PTB7-based organic photodiodes: compatibility of OXCBA as an electron acceptor - Mohd Kamal, Muhammad Alif Ikmal; Roslan, Nur Adilah; Hisamuddin, Syaza Nafisah; Alwi, Siti Anis Khairani; Md Sabri, Amirul Ashraf; Tam, Nguyen Minh; Ahmad Ludin, Norasikin; Bawazeer, Tahani M.; Alsoufi, Mohammad S.; Alsenany, Nourah; Supangat, Azzuliani (Springer, 2023)
Organic photodiodes (OPDs) composed of (poly4,8-bis(2-ethyl-hexyl)oxybenzo1,2-b:4,5-b0dithiophene-2,6-diyl3-fluoro-2-(2-ethylhexy) carbonyl thieno 3,4-bthiophennediyl) (PTB7) as the donor and o-xylenyl-C60-bisadduct (OXCBA) as an acceptor material were investigated. The concentration of the photoactive film blend ratios of PTB7:OXCBA was varied at 1.00:0.25, 1.00:0.50, 1.00:1.00, and 1.00:1.50. The OPD with the 1.00:1.00 ratio showed the best performance, with rise time and fall time of 310 ms and 445 ms, respectively, much faster than most photoactive films. The detector displayed good photocurrent density, fast photo-response time, and high consistency towards the rapid change of light intensity. The enhanced performance was mainly driven by the improvement in the charge extraction efficiency ascribed to the improvement in the interpenetrating network between the interface of the donor and acceptor. It was found that the photodetector exhibits good photo-responsivity of 118 mA/W with specific detectivity of 6.32 × 109 Jones at a bias voltage of −1 V.